Rendimento corporal, composição centesimal e resistência do couro de tilápia Oreochromis niloticus, produzida em viveiros escavados e tanques-rede - SANTOS, V. G. N. (2015)
The objective of this paper was to evaluate the corporal revenues, determine the chemical composition of the filet and evaluate the physical-mechanic resistance of the Nile tilapia leather (Oreochromis niloticus) produced in dug fishponds and cages. The results obtained of the corporal characteristics , the revenues results, the morphometric relations, the chemical composition of the filets and the physical-mechanic tests of the tilapia leather from both raising systems have undergone variance analysis (ANOVA). When statistic differences were observed (p<0,05), the Tukey test was applied in 5% of significance, using the software Statistica7.1. Significant differences were observed (p<0,05) for the average values of corporal characteristics between both raising systems for the total and standard length, total weight, pectoral fin and filet weight. As for the morphometric relations, chemical composition of the filets and the resistance of the leather significant differences were not observed (p>0,05). Therefore it is concluded that the systems did not influence on the corporal revenue, morphometric relations, quality of the meat and in the physical-mechanic tests of the leather.